2014
DOI: 10.1007/s11367-014-0788-0
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental impacts of hybrid, plug-in hybrid, and battery electric vehicles—what can we learn from life cycle assessment?

Abstract: Purpose The purpose of this review article is to investigate the usefulness of different types of life cycle assessment (LCA) studies of electrified vehicles to provide robust and relevant stakeholder information. It presents synthesized conclusions based on 79 papers. Another objective is to search for explanations to divergence and "complexity" of results found by other overviewing papers in the research field, and to compile methodological learnings. The hypothesis was that such divergence could be explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
266
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 433 publications
(280 citation statements)
references
References 90 publications
(106 reference statements)
8
266
0
6
Order By: Relevance
“…All flows under LCA will be standardised for certain product lifetimes or at least a lifetime under which different LCA results may be compared. For a vehicle, LCA calculations reported are usually based on 100,000 to 200,000 km of driven distance, ecoinvent database suggests 150,000 km (Del Duce et al 2014) and in exceptional cases, this can reach 240,000 km (Nordelöf et al 2014). Accordingly, WTW-4 (JEC 2014b) defines a "lifetime of at least 160,000 km" for an electric vehicle.…”
Section: Comparison Of Wtw and Lcamentioning
confidence: 99%
“…All flows under LCA will be standardised for certain product lifetimes or at least a lifetime under which different LCA results may be compared. For a vehicle, LCA calculations reported are usually based on 100,000 to 200,000 km of driven distance, ecoinvent database suggests 150,000 km (Del Duce et al 2014) and in exceptional cases, this can reach 240,000 km (Nordelöf et al 2014). Accordingly, WTW-4 (JEC 2014b) defines a "lifetime of at least 160,000 km" for an electric vehicle.…”
Section: Comparison Of Wtw and Lcamentioning
confidence: 99%
“…A model that uses real-world data compared to using cycle test values produces more realistic energy consumptions, and has added value for research topics relying on consumption data as input. Life Cycle Assessments (LCA) and Total Cost of Ownership (TCO) studies, for example, still use energy consumption based on the New European Drive Cycle (NEDC) [10][11][12] or other standardized cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Most life-cycle assessment (LCA) studies on EVs assumed that EVs are part of the total load of the system and used average emission factors for electricity supply to assess EV environmental impacts (e.g., [1][2][3][4][5][6][7][8]). These studies have found that vehicle use dominates over the vehicle production phase regarding energy consumption and GHG emissions, particularly for fossil-based electricity mixes [8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that vehicle use dominates over the vehicle production phase regarding energy consumption and GHG emissions, particularly for fossil-based electricity mixes [8]. Some studies also addressed the influence of the charging profile in the GHG emissions of EVs, with some reporting that EV charging during off-peak hours results in lower emissions than in peak hours [9][10][11].…”
Section: Introductionmentioning
confidence: 99%